Developmental Dysplasia and Dislocation of the Hip in Adults (Springer Singapore, 2018)
This book provides descriptions of up-to-date treatment options for adult DDH/CDH (Dysplasia and Dislocation of the Hip/Congenital Dislocation of the Hip). It describes the author's modification of peri-acetabular osteotomy for young adult DDH patients, resurfacing arthroplasty for selected patients and total hip arthroplasty for advanced arthritis and dislocation. Untreated high dislocation of the hip in adults are rare in developed countries now. The chapter of total hip describes more than 300 total hips for high dislocation with specific attempt to symmetrize the lower limbs. Techniques are described in detail, which includes ilio-femoral distraction, acetabular reconstruction, femoral osteoplasty, and shortening, derotation and corrective osteotomies. The editors invited several surgeons who are reputed for treating adult DDH with joint salvage and joint replacement to write chapters of this book.